Twist : a novel - McCann, Colum, 1965- (Random House, 2025)
"Anthony Fennell, an Irish journalist and playwright, is assigned to cover the story of the underwater cables that carry the world's information. The sum of human existence--words, images, transactions, memes, voices, viruses--travels through the tiny fiber optic tubes. But sometimes the tubes break at an unfathomable depth. Fennell's literary adventure brings him to the west coast of Africa where he uncovers a story about the raw human labor behind the dazzling veneer of the technological world. He meets a fellow Irishman, John Conway, the chief of mission on a cable repair ship. The mysterious Conway is a skilled engineer and a freediver capable of reaching extraordinary depths. He is also in love with a South African actress, Zanele, who must leave to go on her own journey to London. When the boat is sent up the west coast of Africa to repair a series of major underwater breaks, both men learn that the very cables they seek to fix carry the news that may cause their lives to unravel. At sea, they are forced to confront the most elemental questions of life, love, absence, belonging and the perils of our severed connections. Can we, in our fractured world, reweave ourselves out of the thin, broken threads of our pasts? Can the ruptured things awaken us from our despair?"--